The Normal and Brain Tumor Vasculature: Morphological and Functional Characteristics and Therapeutic Targeting - Guyon, Joris; Chapouly, Candice; Andrique, Laetitia; Bikfalvi, Andreas; Daubon, Thomas (Frontiers in Physiology, 2021)
Glioblastoma is among the most common tumor of the central nervous system in adults. Overall survival has not significantly improved over the last decade, even with optimizing standard therapeutic care including extent of resection and radio-and chemotherapy. In this article, we review features of the brain vasculature found in healthy cerebral tissue and in glioblastoma. Brain vessels are of various sizes and composed of several vascular cell types. Non-vascular cells such as astrocytes or microglia also interact with the vasculature and play important roles. We also discuss in vitro engineered artificial blood vessels which may represent useful models for better understanding the tumor-vessel interaction. Finally, we summarize results from clinical trials with anti-angiogenic therapy alone or in combination, and discuss the value of these approaches for targeting glioblastoma.